2016
DOI: 10.21164/pomjlifesci.16
|View full text |Cite
|
Sign up to set email alerts
|

Odmienne Środowiska Egzystencji Życiowej Jako Czynnik Różnicujący Funkcje Poznawcze I Czynności Dnia Codziennego W Grupie Osób Powyżej 50. Roku Życia

Abstract: Introduction: The aim of the dissertation was to compare the psychophysical state of people over 50 years of age from different societies.Material and methods: The first group consisted of 30 care home residents, the second group consisted of 30 participants of Active Senior Fair. In the research, two scales were applied: Mini­‍‑Mental State Examination, measuring the mental state, and Instrumental Activity of Daily Living, measuring agility in the field of complex everyday tasks.Conclusiona: The study indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Gębska et al demonstrated that the life of elderly individuals is highly dependent on the surroundings in which they live. These researchers concluded that elderly people who actively participate in social activities demonstrated an improved psychophysical state [10] Currently there is a growing interest in the correlation between physical activity and the health Key words: status of elderly individuals [11]. Regardless of age, insufficient physical activity constitutes one of the most problematic issues of contemporary society [12].…”
Section: Introductionmentioning
confidence: 99%
“…Gębska et al demonstrated that the life of elderly individuals is highly dependent on the surroundings in which they live. These researchers concluded that elderly people who actively participate in social activities demonstrated an improved psychophysical state [10] Currently there is a growing interest in the correlation between physical activity and the health Key words: status of elderly individuals [11]. Regardless of age, insufficient physical activity constitutes one of the most problematic issues of contemporary society [12].…”
Section: Introductionmentioning
confidence: 99%